Prognostic role of systemic inflammation response index (SIRI) in patients with pancreatic cancer: a meta-analysis - Shen, Huifen; Zuo, Fei (Frontiers in Oncology, 2024)
BackgroundThe significance of the systemic inflammation response index (SIRI) in predicting the prognosis of patients with pancreatic cancer (PC) has been extensively explored; however, findings remain controversial. As such, this meta-analysis was performed to more precisely determine the utility of the SIRI in predicting PC prognosis.MethodsA comprehensive literature search of the PubMed, Web of Science, Embase, and Cochrane Library databases for relevant studies, published up to June 25, 2024, was performed. The primary and secondary endpoints were overall survival (OS) and progression-free survival (PFS), respectively. The prognostic utility of the SIRI in predicting PC prognosis was estimated by calculating pooled hazard ratios (HRs) and corresponding 95% confidence intervals (CIs).ResultsSeven studies comprising 1160 patients were included in the present meta-analysis. Pooled findings revealed that elevated SIRI was as a prominent prognostic marker of OS (HR 2.40 [95% CI 1.88–3.05]; p<0.001) and PFS (HR 1.95 [95% CI 1.19–3.21]; p=0.008) in patients diagnosed with PC. According to subgroup analysis, the SIRI remained an outstanding prognostic marker for OS, irrespective of region, sample size, study center, study design, TNM stage, cancer type, cut-off value, treatment, or survival analysis type (all p<0.05). Moreover, based on subgroup analysis, the SIRI demonstrated significant utility in predicting PFS, irrespective of region and threshold value (p<0.05).ConclusionResults of the present meta-analysis revealed that an increased SIRI significantly predicted OS and PFS in patients diagnosed with PC. Considering its cost-effectiveness and availability, the SIRI may be a promising biomarker for predicting prognosis in patients with PC.